The Synthesis of Alkaloids Using Transition-Metal-Catalyzed Intramolecular Amination Reactions - Ohno, Hiroaki; Chiba, Hiroaki; Inuki, Shinsuke; Oishi, Shinya; Fujii, Nobutaka (Synlett, 2014)
Transition-metal-catalyzed reactions have the potential to provide significant improvements to the syntheses of complex target molecules. These reactions can be used to achieve a variety of different atom-economical transformations and cascade reactions and, therefore, provide access to synthetic strategies that would otherwise be unavailable using classical organic chemistry. To exemplify the utility of the latest transition-metal-catalyzed reactions for the construction of important target structures, we have been involved in the total synthesis of natural products bearing widely known chemical scaffolds. In this account, we report our recent studies on the use of a palladium-catalyzed cascade cyclization reaction and a gold(I)-catalyzed hydroamination reaction for the construction of the core structures of alkaloids, as well as their application to the total syntheses of lysergic acid, lysergol, isolysergol, and quinocarcin.1 Introduction2 Ergot Alkaloid Synthesis2.1 Construction of the Core Structure by Palladium-Catalyzed Cascade Cyclization2.2 Asymmetric Total Syntheses of (+)-Lysergic Acid and Related Alkaloids3 Quinocarcin Synthesis3.1 Construction of the Core Structure by Gold-Catalyzed Hydroamination3.2 Asymmetric Total Synthesis of (–)-Quinocarcin4 Concluding Remarks
Keywords: total synthesis; palladium; gold; alkaloids; atom economy